692Association of drinking habits with TXNIP DNA methylation levels in leukocytes among general Japanese population. (2nd September 2021) - Maeda, Keisuke; Yamada, Hiroya; Munetsuna, Eiji; Fujii, Ryosuke; Yamazaki, Mirai; Ando, Yoshitaka; Mizuno, Genki; Ishikawa, Hiroaki; Ohashi, Koji; Tsuboi, Yoshiki; Hashimoto, Shuji; Hamajima, Nobuyuki; et al.
Abstract: Background: Thioredoxin-interacting protein (TXNIP) inhibits the activity of thioredoxin (TXN), leading to increased oxidative stress. Expression of the TXNIP gene is regulated by DNA methylation. However, no study has reported the influence of lifestyle factors on TXNIP DNA methylation. Our goal was to determine the association between drinking habits and TXNIP DNA methylation levels in the general Japanese population. Methods: We conducted a cross-sectional study of 404 subjects (176 males and 228 females) participating in a health examination. Subjects were divided into non-, moderate (male: 1-39g; female: 1-19g ethanol/day) and heavy (male: ≥40g; female: ≥20g ethanol/day) drinkers based on self-reported drinking habits. We used a pyrosequencing assay to determine TXNIP DNA methylation levels in leukocytes. Results: Among men, the mean TXNIP DNA methylation level in heavy drinkers (73.2%) was significantly lower than that in non- and moderate drinkers (non: 76.7%, p <0.001; moderate: 75.8%, p =0.024). In multiple linear regression analysis adjusted for confounding factors, TXNIP DNA methylation levels showed significant negative association with alcohol consumption per day and cumulative alcohol consumption in male current drinkers. Conclusions: We found that heavy drinkers had TXNIP DNA hypomethylation compared to non- and moderate drinkers in men. Moreover, alcohol consumptions were also negatively associated with TXNIP DNA methylation levels in male current drinkers. Key messages: Heavy drinkers had decreased levels of TXNIP DNA methylation compared to non- and moderate drinkers in men.